The Long-Run Performance of Initial Public Offerings - Ritter, Jay R. (Journal of Finance, 1991)
The underpricing of initial public offerings (IPOs) that has been widely documented appears to be a short-run phenomenon.Issuing firms during 1975-84 substantially underperformed a sample of matching firms from the closing price on the first day of public trading to their three-year anniversaries.There is substantial variation in the underperformance year-to-year and across industries, with companies that went public in high-volume years faring the worst.The patterns are consistent with an IPO market in which (1) investors are periodically overoptimistic about the earnings potential of young growth companies, and (2) firms take advantage of these "windows of opportunity."NUMEROUS STUDIES HAVE DOCUMENTED two anomalies in the pricing of initial public offerings (IPOs) of common stock: (1) the (short-run) underpricing phenomenon, and (2) the "hot issue" market phenomenon.Measured from the offering price to the market price at the end of the first day of trading, IPOs produce an average initial return that has been estimated at 16.4%.1Furthermore, the extent of this underpricing is highly cyclical, with some periods, lasting many months at a time, in which the average initial return is much higher.2In this paper, I document a third anomaly: in the long-run, initial public offerings appear to be overpriced.Using a sample of 1,526 IPOs that went public in the U.S. in the 1975-84 period, I find that in the 3 years after going public these firms significantly underperformed a set of comparable firms matched by size and industry.